Barrgh-gaining with Somali Pirates - Olaf J. de Groot; Matthew D. Rablen; Anja Shortland (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
Ransoms paid to Somali pirates are drifting upward and negotiation times are increasing, yet there is huge variation in bargaining outcomes across shipowners. We use a unique dataset of 179 Somali hijackings, and an underlying theoretical model of the bargaining process based on detailed interviews with ransom negotiators, to analyze the empirical determinants of ransom amounts and negotiation lengths. We find that ransom amount and negotiation length depend on the observable characteristics of both pirates and ships and on the "reference ransom" established by previous ransom payments for a specific ship type. International naval enforcement efforts have driven up ransom amounts. We also observe a "hump-shape" in ransoms, with relatively low ransoms being paid following both short and very long negotiations, and the highest ransoms paid following intermediate length negotiations.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: K42; P48; 330; Piracy; ransom; duration; bargaining; law enforcement; Somalia